Biochemical responses in ‘Kent’ mango grown in Brazilian semi-arid region under different doses of triacontanol - Luciana G. Sanches; Alana J. da S. Santos; Daniel de A. Carreiro; Jenilton G. da Cunha; Jackson T. Lobo; Ítalo H. L. Cavalcante; Vespasiano B. de Paiva Neto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The management adopted for the mango crop requires that, at a certain stage, the irrigation depth should be reduced to promote a more uniform flowering. In regard to that, it is necessary to introduce new alternatives that mitigate the harmful effects of abiotic stress and that promote greater fruit yield. Therefore, the present study aimed to evaluate the influence of triacontanol on the levels of organic solutes, antioxidant enzymatic activity, and production of ‘Kent’ mango under Brazilian semi-arid conditions. The experiment was carried out for two consecutive years, 2018 and 2019, in a commercial orchard located at the DAN Farm, Petrolina-PE. The experimental design used was randomized blocks, with five treatments and four replications, evaluating four plants per plot. The treatments consisted of triacontanol doses: 0 (control treatment), 3.75; 7.50; 11.25, and 15.00 ppb per plant. Two consecutive harvests (2018 and 2019) were evaluated during the stages of branch maturation (2019 only), floral induction, full flowering, and initial fruiting. Foliar application of triacontanol positively favored the contents of total amino acids, free proline, total proteins, and activity of the enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT). There was an increase in production of 50.85% (dose - 11.25 ppb) and 64.95% (dose - 10.50 ppb) in the 2018 and 2019 crop years, respectively.